Detecting beef meatball contamination with polymerase chain reaction - Hoda A. (Biotika, 2017)
The objective of the study was to describe how much rat and swine primer developed from cytochrome b could detect rat and pork in processed beef products sold in North Maluku. The settings of the study were the traditional markets and supermarkets in several cities in North Maluku such as Ternate, Tidore Kepulauan, West Halmahera, North Halmahera, Central Halmahera, South Halmahera, East Halmahera, Sula Island and Morotai Island. The data collection lasted between May and June, 2015. The samples were analyzed in the Biotechnology Lab of Unkhair in July, 2015. To detect rat and swine DNA, the researchers used the PCR (Polymerase Chain Reaction) method with Top Taq master mix Kit kit (250) (Catalog no. 200403) Swine Primer: Forward: 5'CTA CAT AAG ATAT ATC CAC CAC A 3 'Reverse: 5' ACA TTG TGG GAT CTT CTA GGT 3 'Product size: 290 bp. Rat Primer: forward SIM (5'-GACCTCCCAGCTCCATCAAACATCTCATCTTGATGAAA-3'). Reverse (5'GAATGGGATTTT GTTGGAGTTT-3 '). Out of 41 samples, sample 3, 4 and 5 taken in Jailolo contained rat DNA (positive); the samples were amplified with 499 base pair length (bp). In addition, sample 2, 7, 8 and 10 from Ternate as well as sample 4 from Morotai Island was also found positive (containing rat DNA). In terms of swine DNA, all of the samples came back negative. The amplification showed that none of the meatball samples contained pork. No pig DNA was amplified in the gel.